The application of digital signal processing to the modelling and alleviation of auditory impairment - O'Reilly, Derek B. (Trinity College (Dublin, Ireland). Department of Electronic & Electrical Engineering, 2001)
This work is concerned with the development of digital signal processing models of the unimpaired and impaired human auditory system with a view towards the development of signal processing strategies for the alleviation of auditory impairment.
Keywords: Electronic and Electrical Engineering, Ph.D.; Ph.D. Trinity College Dublin